Procedural inaccuracies and the issue of determining real estate value in court proceedings - Sokół, Krzysztof; Sobolewska-Mikulska, Katarzyna (Wydawnictwa AGH, 2023)
The aim of the article is to analyze proceedings resulting in the determination of the value of real estate and an attempt to capture the reasons why the judicial determination of its value sometimes requires alternative or subsequent opinions on the value of the property by another expert valuer. For the purposes of this article, the method of examining individual cases was generally used, i.e. two exemplary court cases in which the main opinions, supplementary opinions, subsequent supplementary opinions, and subsequent main opinions were prepared and where an expert valuer was additionally summoned to a hearing in order to directly submit a supplementary opinion to the court.
Geomatics and Environmental Engineering
Bibliogr. s. 49-51.
Keywords: determination of the value of real estate; expert valuers; court proceedings